Climate Change Policy and Mental Health - Douki, Stamatina; Tzagkarakis, Stylianos Ioannis; Spyridakis, Emmanouil (HAPSc Policy Briefs Series, 2021)
Climate change is a major problem that modern society faces. The impact of human activity on the environment, worldwide, has had irreversible negative effects on daily lives as well as on mental health. The present study aims to investigate climate change, its effects on mental health of the population and the development of strategies to address the eminent negative consequences. The methodology included literature and research data review, which were collected through Google Scholar, Pub-med online database, articles, journals and dissertations. This study makes evident that climate change affects the mental health of the population and requires further investigation and planning in order to implement appropriate information and consultation programs as well as to promote the adoption of habits and behaviours in order to address and reduce the negative environmental consequences.